Łacińskie epitafia w farze poznańskiej - Rosół, Rafał (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The paper deals with three Latin epitaphs that are located in the Parish Church in Poznań (the former Jesuit Church). These inscriptions honour Stanisław Grabski (ca. 1633–1693), Kasper Drużbicki (1590–1662) and Józef Pawłowski (1698–1759). The author provides a critical edition of the inscriptions, their Polish translations, as well as a commentary.